PEMANFAATAN APLIKASI AI DAN WEBSITE E-KATALOG UNTUK DIGITALISASI UMKM DESA "PASEBAN KAWIS" - auliya, yudha alif; Muhammad, Abdurrohman Qoim Haqqi; Kurniawan, Muhammad Rafi; Kinanti A, Keysha; Hadist , Nurul (Dedication : Jurnal Pengabdian Masyarakat, 2025)
The PASEBAN KAWIS program was designed to digitize MSMEs in Kalibaru Manis Village through an Artificial Intelligence (AI)-based educational application and an e-catalog website. The background for this activity was low digital literacy, limited market access, and a lack of standardization of local products such as coffee, cassava, and Etawa goat milk. The implementation method uses a participatory approach involving village officials, BUMDes, MSME actors, and students, with stages of needs analysis, application and e-catalog development, training, mentoring, and implementation evaluation. The results of the activity show an increase in participants' digital skills, ease of creating promotional content, and expanded market access for village products. The e-catalog website displays a structured product catalog, while the AI chatbot supports interactive learning. The program outputs include an AI education application, an e-catalog website, an MSME digitization module, and an increase in product turnover of ±20%. In conclusion, PASEBAN KAWIS is effective in strengthening digital literacy, product branding, and building a village digital entrepreneurship ecosystem.